Sosialisme Religius Sebagai Jalan Keadilan Sosial Perspektif Nurcholish Madjid - NurdzaArsyiMaulana, Nurdza Arsyi Maulana; Lestari, Ayu (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2025)
This research is a study of the concept of religious socialism as a way of social justice from the perspective of Nurcholish Madjid contained in his works, especially Islam Kemodernan and Ke-indonesian. This research seeks to explore aspects of Nurcholish Madjid's thought and the relevance of his thought in contemporary Indonesia. The method used by the author in this research is analytical-descriptive, and conducts library research, especially on the book Islam Kemodernan and Ke-indonesiaan. In addition, the author also looks for other sources in the form of books, articles, magazines and journals that are still relevant to this research. Cak Nur proposed the concept of religious socialism that integrates the values of socialism with tawhid to achieve social justice. Cak Nur explained that justice is not just a moral principle, but a mandate from God that must be fought for by every individual and society.